Robocasting of reaction bonded silicon carbide/silicon carbide platelet composites - Wahl L. Larissa; Weichelt M. Michelle; Goik Ph. Philip; Schmiedeke S. Samuel; Travitsky (Travitzky) N. Nakhum (2021, 2021)
Title screen